PROXIMATE COMPOSITION OF SNAKEHEAD NOODLE (Channa striata) WITH THE ADDITION OF PORANG FLOUR (Amorphophallus oncophyllus) - Hendra Mario Silaban; Dahlia Dahlia; Dewita Dewita (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTThis study was aimed to determine proximate characteristic of snakehead fish (Channa striata) noodles with the addition of porang flour (Amorphophallus oncophyllus).  The research method used was the addition of 9% porang flour (A. oncophyllus). Parameters of analysis consisted of moisture content, protein, fat, ash, total fiber, and carbohydrate (proximate).  The results showed that snakehead fish noodles added with 9% porang flour had protein, ash, fat and moisture content; 11,4%; 2.15%; 2.06%; 53.57%, respectively . The total fiber and carbohydrate content of snakehead fish noodles added with porang flour were 5.03% and 23.06%, respectively. The moisture content, protein, fat and carbohydrate content of snakehead fish noodles have been according the 1992 Indonesian National Standard No. 01-2987. Keywords: noodles, proximate, porang flour, snakehead fish.